Pelatihan Objektivitas dan Pentingnya Learning dalam Pengasuhan Orang Tua terhadap Anak - Hema Dayita Pohan; Erik Saut H Hutahaean; Yuarini Wahyu Pertiwi; Djuni Thamrin; Tiara Anggita Perdini (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING OF OBJECTIVITY AND THE IMPORTANCE OF LEARNING IN PARENTING FOR CHILDREN. Family is a group consisting of individuals bound by marriage or blood relationship consisting of parents (father, mother) and children. In the family, the biggest role is parents. Parents have an obligation to educate, and raise children as well as possible which in the process involves parenting. In parenting, parents must pay attention to the elements of objectivity and learning, namely parents must be able to assess and pay attention to children according to their portions and their willingness to learn. This activity is carried out to support parents' knowledge about the objective and learning elements. The audience is the women of the RPTRA community as many as 47 people. Submission of objective and learning materials will be delivered through lecture teaching methods and also distributing pre-test and post-test forms. As a result, there were many variants of answers from the audience, and this activity increased their understanding of good parenting. This activity is still limited to the level of knowledge and understanding, there is still a need for more effective follow-up activities so that they can be applied in life.